Influence of High Voltage Electrostatic Field (HVEF) on Vigour of Aged Rice (Oryza sativa L.) Seeds - Li Jian, Liao Ruijin, Wang Guixue, Huang Junli, Gao Weina (Journal of Phytology, 2009)
The vigour restoration of aged rice seeds is of great significance in agriculture. This paper studied the biological effects of high voltage electrostatic field (HVEF) on aged rice seeds, including dry seeds and wet seeds soaked in sterile deionized water for 24 hours. The results showed that HVEF slightly affected the vigour of the aged dry rice seeds while the seed vigour and seedling growth of the aged wet rice seeds were significantly improved. The germination rate and germination potentiality also showed moderate improvement after exposure to HVEF with electric intensity less than t 450 kV•m-1. Compared to control, the vigour index of aged wet rice seeds was increased 31.96%. No significant effects of HVEF on dry aged rice seeds were found.